Enhanced active motion of Janus colloids at the water surface1. Issue 37 (7th October 2015) - Wang, Xiaolu; In, Martin; Blanc, Christophe; Nobili, Maurizio; Stocco, Antonio
<x xml:space="preserve">Abstract</x> Self-propelled Janus colloids show enhanced active motion when trapped at the water surface. Trajectories are more directional and velocities are higher than those in the bulk. The confinement effect given by the air–water interface strongly reduces the rotational motion of the colloid while not hindering self-propulsion.